ANNUAL DYNAMICS OF DISSOLVED AND PARTICULATE ORGANIC MATTER (C and N) IN A SUB-TROPICAL FLUVIAL-LACUSTRINE SYSTEM (CIMA LAKE - BRAZIL) - Calasans, Claudia; Pedrosa, Paulo; Rezende, Carlos Eduardo (Geochimica Brasiliensis, 2011)